The Creation of FirstCity Financial Corporation: A Clinical Study of the Bankruptcy Process - Rao, Ramesh K. S.; White, Susan (Senate Hall Academic Publishing, 2005)
This paper examines the bankruptcy of First City Bancorporation of Texas and its subsequent emergence, through a merger, as FirstCity Financial Corporation (FCFC). It illustrates several interrelated issues: a) how informational asymmetries and disagreements among the various claimants were efficiently resolved through the use of a Court’s Expert, b) why a merger was critical for the success of the reorganization plan, c) the process by which the claims were valued, and d) the steps taken by the Court to ensure that the “best interests test” was satisfied under the reorganization plan.
Keywords: bankruptcy; confirmation; FirstCity; best interests test; reorganization